Enforcement Of Criminal Law Against Abuse Of Immigration Permit According To Republic Of Indonesia Law No. 6 Of 2011 Concerning Immigration - La Ode Bunga Ali (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The scope of the visa-free facility is too broad which includes tourism, socio-cultural, and business activities, which was originally intended to strictly regulate visa-free facilities, but after the provision of visa-free facilities in the BVKS which has a wider scope, violations of the visa-free facility are still found. that. So that the aims and objectives of Free Social Visit Visa (BVKS) as a substitute for Free Tourist Visa (BVW), were not achieved, instead they were used by foreigners as a way for illegal immigrants to enter Indonesia. However, the General Explanation of Law No. 6 of 2011 concerning immigration emphasizes that for foreigners, services and supervision in the field of immigration are carried out with a